Acoustic signal of silent tracheal aspiration in children with oropharyngeal dysphagia. (2nd October 2018) - Almeida, Sheila T. de; Ferlin, Elton L.; Maciel, Antonio C.; Fagondes, Simone C.; Callegari-Jacques, Sidia M.; Fornari, Fernando; Sérgio G. Silva, de Barros; Goldani, Helena A. S.
Abstract: Objetive: The aim of this study was to characterize the acoustic signal of silent tracheal aspiration in children with oropharyngeal dysphagia (OPD).Method : Thirty-two children with OPD were examined with combined digital cervical auscultation (DCA) and videofluoroscopic swallow study (VFSS). Power spectral density (PSD, in 1/√Hz) of the acoustic signal from a sequential series of five liquid swallows was used for comparisons between children who silently aspirated and children who did not aspirate on VFSS. Fourteen children were excluded due to either DCA/VFSS artifact or non-silent aspiration (cough, choking).Results : The remaining 18 participants (median age 6 years, range 2–12.8) were classified based on VFSS as aspirators ( n = 8) and non-aspirators ( n = 10). The PSD curve of aspirators presented an ascending pattern (1st vs. 5th deglutition: 695.2 vs. 4421.9 1/√Hz), while the curve of non-aspirators was flat (1st vs. 5th deglutition: 509 vs. 463.4 1/√Hz), with marked differences being observed from the 3rd measure onwards ( p < .001). In this study, DCA was able to identify silent tracheal aspiration in children with OPD.Conclusion: This non-invasive technique identified aspiration by an increase in the PSD curve in aspiration sounds.